Chlorpropamide-alcohol flushing: a definition of its relation to non-insulin-dependent diabetes. Issue 6151 (2nd December 1978) - Pyke, D A; Leslie, R D
Abstract : The single-challenge test for chlorpropamide-alcohol flushing (CPAF) was used to study two groups of patients with non-insulin-dependent diabetes and a family history of the disease who were distinguished only by their age at diagnosis (under and over 30). Their relatives were also studied. The proportions of patients showing CPAF in both groups were similar, and the family histories suggested dominant inheritance. When offspring of diabetics in whom the disease was diagnosed early were studied CPAF seemed to precede the appearance of diabetes. We conclude that the patients in both groups had the same, distinct syndrome, which is characterised by diabetes diagnosed at any age that is inherited as an autosomal dominant trait and associated with CPAF. This syndrome, which constitutes about one-fifth of all cases of non-insulin-dependent diabetes, may be detected with a single-challenge CPAF test before the onset of glucose intolerance. CPAF therefore acts as a genetic marker for the syndrome.